Contextual source information modulates neural face processing in the absence of conscious recognition: a threat-of-shock study - Schellhaas, Sabine; Arnold, Nina Rebecca; Schmahl, Christian; Bublatzky, Florian (Neurobiology of learning and memory, 2020)
Often the source of information is as important as the information itself. The present study examined the impact of contextual threat and safety signals (source information) on memory encoding and recognition of faces (item information). In two experimental sessions, 30 participants viewed neutral face pictures. In the encoding session, 60 faces were presented with contextual background colors (blue or green, 30 pictures each) which were verbally instructed to signal either threat-of-shock or safety. In the recognition session, the 60 old faces intermixed with 30 new faces were shown while a combined old/new recognition and source memory task was performed. During the encoding session, face processing varied as a function of contextual source information. Confirming successful threat-of-shock manipulation, threatening compared to safe face-context compounds revealed differential neural processing (early parieto-occipital and late fronto-central negativity) as well as pronounced threat ratings. During the recognition session, participants had serious problems identifying old from new faces with poor source memory. Intriguingly, however, brain activity differentiated previously seen faces from newly presented pictures (old/new ERP effect). Moreover, old faces presented within a threat context were associated with distributed late negativities compared to old safe faces. Thus, threat effects not only emerged during face encoding (incidental learning) but also during face recognition, although no valid judgements could be made regarding the threatening or safe sources. These findings support the notion that contextual source information critically modulates person perception and recognition as a form of an expectation based remembering in the absence of conscious recognition.